GENERAL CHARACTERISTICS AND ESSENCE OF SOCIAL PROTECTION INSTITUTIONS IN ISLAM (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The unique expression of the harmony and inseparability of religion, morality, and law in Islam is determined, on the one hand, by the regulation of social relations, and on the other hand, by the relationship (worship) of Muslims with Allah. The divine application and religious-moral foundations of Sharia are reflected in the understanding of fiqh, that is, Islamic law.